Funkcjonowanie uczniów należących do grup rówieśniczych i bez przynależności grupowej w relacji ja-zadanie = Functioning of students belonging to peer groups and without group membership in the relation me-task - Fudali, Maria; Dziubak, Aneta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The functioning of an individual in the role of a student depends largely on group membership. Junior high school students who belong to peer groups in class have a positive attitude to school. For them it is a place to meet their peers who provide them with help and support indispensable to the proper functioning in the role of a student. Such students more often feel good and safe at school. Few students who are the members of peer groups develop their hobbies and interests. They prefer the company of their peers and spend their free time with them.
Keywords: młodzież gimnazjalna; gimnazjaliści; grupa rówieśnicza; funkcjonowanie społeczne